2018
DOI: 10.1590/198053145588
|View full text |Cite
|
Sign up to set email alerts
|

Género y práctica de ejercicio físico de adolescentes y universitarios

Abstract: RESUMEN El objetivo ha sido investigar las diferencias de género y edad con relación a la práctica de ejercicio físico en una muestra de adolescentes y universitarios. Se aplicó un cuestionario a 442 estudiantes y se realizó grupos de discusión con 75 participantes de la Provincia de Toledo. Se ha observado que los chicos practican más ejercicio físico e invierten más tiempo en la práctica, independientemente de la edad. Los resultados apuntan que los objetivos y la motivación para la práctica de ejercicio fís… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
2
2
0
2
Order By: Relevance
“…This is complemented by the mean number of years running for men (10.9 years), compared to that found in women (5.7 years). These findings are in line with a previous study on adolescents that reported that males engage in more physical activity for longer periods of time than females [20]. Further studies with limited age groups are suggested to thoroughly explore these relationships and detect variations between young adults, middle-aged, and older adult runners.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is complemented by the mean number of years running for men (10.9 years), compared to that found in women (5.7 years). These findings are in line with a previous study on adolescents that reported that males engage in more physical activity for longer periods of time than females [20]. Further studies with limited age groups are suggested to thoroughly explore these relationships and detect variations between young adults, middle-aged, and older adult runners.…”
Section: Discussionsupporting
confidence: 91%
“…Given that, in terms of body composition, there are differences in the proportion of fat mass and muscle mass between the sexes [19], it is expected that there will be differences in exercise performance, which may be accentuated by gender aspects and traditional roles. It has been observed that more men engage in physical exercise than women, and men also dedicate more time to the practice than women [20]. Women present greater body dissatisfaction [21] and report lower scores of psychological well-being in the dimensions of self-acceptance and autonomy; however, in positive relationships with others and personal growth, they score higher than men [22], while men obtain higher scores in emotional intelligence [16,23].…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, various research has pointed out higher participation of females in physical activities. However, these studies indicate that girls tend to choose moderate-intensity activities, such as household chores and dancing, while male adolescents dedicate considerably more time to vigorousintensity physical activities, according to identified findings (Aguilar et al, 2018;Martínez et al, 2019;Oliveira and Parra, 2018;Sallis et al, 2018;Taverno et al, 2013), although in our study, the tendency to engage in sports is higher in females in all aspects.…”
Section: Discussionsupporting
confidence: 57%
“…This finding was also confirmed by a study done in 2018 on Spanish adolescents and young adults. 29 Some authors have attributed these differences to cultural stereotypes existing between both genders referring to the practice of physical activity. 30 In addition, males at this stage of life are preoccupied with improving their external masculine appearance.…”
Section: Discussionmentioning
confidence: 99%